Modification of Plasmids and Cry Genes of Bacillus Thuringiensis subsp. kurstaki Lid-I After Treatment With Ethymethanosulfonate (EMS) and UV Light - Jusuf, Eddy (Research Center for Biotechnology - Indonesian Institute of Sciences (LIPI), 2004)
Bacillus thllringiensis subsp. kllrstaki HD-J is a potential insecticidal bacterium producing five type of a -endotoxin crystal proteins. This bacterium is widely commercialized due to its wide spectrum toxicity against both Lepidopteran and Dipteran larvae . The objective of this work was to create autolysin deficient mutant causing cell fails to lyse. This mutant yield intact cell s within spore and a -endotoxin crystal protein protected inside, from which an undamaged active bio-insecticide wou ld be obtained . Two methods of mutagenesis, 2ry( of ethylmethanosulfonate and 10, 25, and 50 second of UV light expo ure, resu lted in mor loss of motility) mutation. Observation showed that 14 of 20 survived mutants have lost some of its plasmids (varied from one to five). wh ile the other six maintained their plasmids. By employing the polymerase chain reaction (PCR) the change on the cry genes was studied. Â